Evaluation of the Multifaceted Impact of Hypothyroidism on Metabolic Components and Quality of Life - Shaji, Bipin; Joel, Juno Jerold; Sharma, Raghava; Shetty, Shraddha (International Journal of Pharmaceutical Investigation, 2025)
Background Hypothyroidism is characterized by an underactive thyroid gland. As thyroid hormones are essential for regulating metabolism, disruptions in secretions can cause metabolic syndrome. This study is to assess the relationship of hypothyroidism with metabolic components and quality of life. Materials and Methods A cross-sectional study was conducted over a year in the department of general medicine of a tertiary care hospital with 200 patients diagnosed with hypothyroidism with metabolic syndrome. Metabolic syndrome was determined using modified NCEP ATP III criteria (2005 revision). The study parameters were Thyroid Hormones (TSH, T3 and T4), metabolic components and quality of life (assessed using the WHOQOL BREF questionnaire). Spearman's correlation analysis was used to determine the relationship between TSH and metabolic components. Results Thyroid Stimulating Hormone (TSH) exhibited a significant positive correlation with BMI (R: 0.07, p: 0.02), systolic blood pressure (R: 0.18, p: 0.008), triglycerides (R: 0.15, p: 0.03) and fasting blood sugar (R: 0.13, p: 0.05) and a negative correlation with High-Density Lipoprotein (R: -0.14, p: 0.04). Regarding quality-of-life domains, TSH has a significant negative correlation with the physical domain (R: -0.18, p: 0.08). Conclusion Hypothyroidism is associated with body mass index, waist circumference, blood pressure and triglycerides but has a negative relationship with high-density lipoprotein. Patients with hypothyroidism with metabolic syndrome experience a poor quality of life, especially in the physical domain.
Keywords: Hypothyroidism; Metabolic syndrome; Thyroid stimulating hormone; Quality of life